Factors Influencing Students’ Decisions to Engage in Entrepreneurship (A Case Study of Entrepreneurship Students at ITBM Polman) - Suriana , Suriana; Albar , Albar; Adisaputra , Whisnu (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2025)
This study aims to identify and analyze the factors influencing students' decisions to pursue entrepreneurship, with a focus on students of the Entrepreneurship Study Program at ITBM Polman. Employing a mixed-methods approach, data were collected through in-depth interviews and quantitative instruments administered to 30 randomly selected respondents. The findings indicate four primary factors that influence entrepreneurial decision-making: economic and business opportunities (15.93%), education (15.76%), social environment (15.7%), and personality traits (15.36%). Economic motives and the availability of business opportunities emerged as the most dominant drivers, followed by educational and social support factors that shape students’ entrepreneurial mindset and motivation. Although personality factors contributed the least, they play a critical role in fostering confidence and resilience in entrepreneurial activities. These findings suggest that students’ decisions to engage in entrepreneurship are the result of a complex interaction between internal and external factors. Therefore, entrepreneurship education strategies should adopt a comprehensive, experience-based approach supported by a socially conducive environment.